Translating Policies Into Practice: A Framework to Prevent Childhood Obesity in Afterschool Programs. Issue 2 (March 2013) - Beets, Michael W.; Webster, Collin; Saunders, Ruth; Huberty, Jennifer L.; ,
Afterschool programs (3-6 p.m.) are positioned to play a critical role in combating childhood obesity. To this end, state and national organizations have developed policies related to promoting physical activity and guiding the nutritional quality of snacks served in afterschool programs. No conceptual frameworks, however, are available that describe the process of how afterschool programs will translate such policies into daily practice to reach eventual outcomes. Drawing from complex systems theory, this article describes the development of a framework that identifies critical modifiable levers within afterschool programs that can be altered and/or strengthened to reach policy goals. These include the policy environment at the national, state, and local levels; individual site, afterschool program leader, staff, and child characteristics; and existing outside organizational partnerships. Use of this framework and recognition of its constituent elements have the potential to lead to the successful and sustainable adoption and implementation of physical activity and nutrition policies in afterschool programs nationwide.